Experiential Learning in the Digital Context: An Experimental Study of Online Cultural Intelligence Training - Kirste, Laura; Holtbrügge, Dirk (Journal of Teaching in International Business, 2019)
Digital transformation has opened novel opportunities for educators to approach the challenges of educating tomorrow's business leaders and managers. New methods of instruction such as blended learning and e-learning allow to cater better to a generation of digital natives and to enhance their learning ability. In the fast-moving business world, different cultures become increasingly intertwined which calls for managers who can function effectively in situations characterized by cultural difference. Hence, IB educators need to provide intercultural learning opportunity to a generation that lives on the intersection of the digital and analogue world. This paper presents and tests an approach to intercultural training by translating experiential teaming into a digital context. Drawing on the results, enhancements and future directions for IB scholars and educators are offered.
CRIS-Team WoS Importer:2019-10-15
Keywords: Kulturelle Vielfalt